Shelf-Life Prediction of Fermented Cassava Dodol Using the Accelerated Shelf-Life Testing Approach - Raini Panjaitan; Erlies Patricia Ramandey; Jhon Marthali Simamora; Baiq Amarwati Tartillah; Jeirel Wattilete; Nurlita Dianingsih; Nadwi Lestari (PAKIS JOURNAL INSTITUTE, 2026)
Fermented cassava dodol is a semi-moist food product that is susceptible to quality changes during storage due to increased moisture content and various deterioration reactions. This study aimed to estimate the shelf life of fermented cassava dodol using the Accelerated Shelf-Life Testing (ASLT) method with a critical moisture content approach and moisture sorption isotherm curve. The research stages included the determination of initial moisture content, critical moisture content, and equilibrium moisture content, as well as sorption isotherm modeling using the Chen-Clayton, Henderson, Halsey, Caurie, and Oswin models. Critical moisture content was determined based on the acceptance level of semi-trained panelists regarding product appearance during storage at a relative humidity (RH) of 76%. The results showed that the initial moisture content and critical moisture content of the product were 0.2205 and 0.2427 g H₂O/g solids, respectively. The obtained moisture sorption isotherm curve exhibited a Type II sigmoid pattern. Based on the evaluation of the Mean Relative Deviation (MRD) value, the Henderson model provided the best fit, with an MRD value of 3.7. Shelf-life calculation using the Labuza equation resulted in an estimated shelf life of 64.07 days, or approximately two months, under room temperature conditions. The information obtained from this study can be used as a basis for shelf-life determination, packaging selection, and management of storage and distribution systems to maintain product quality during the marketing period.